STONES, WORDS, IMAGES - Radu Lilea, Mabe Bethônico and (Design/Arts/Culture, 2023)
Cultural memory, as viewed by historian Alexander Etkind, influenced by the world of computers, from where he takes this blatant yet effective reference, is binary: there is a “soft memory” preserved mostly in texts, and a “hard memory” stored primarily in monuments (Etkind, 2013, p. 177). His perspective on how cultural memory crystallizes, functions and then moulds people’s lives and communities was laid out in a study devoted to Soviet cultural heritage, particularly to those memorial practices engendered by an unburied past which always seems to be resurfacing. It is precisely this way of understanding memory, as an interconnected system whose parts can only work together, that can be further applied beyond the cultural space presented in Etkind’s book. This is, in fact, quite obvious in the works of Mabe Bethônico, a Brazilian visual artist which brought to my mind this insightful way of perceiving cultural memory. Her art projects explore and probe into the veins descending deep into both her country’s past and the earth’s belly – historical and geological veins that, under contemplation, take on more than just a literal meaning. They acquire, simultaneously, new metaphorical and universal interpretations, rendering the artist’s work extremely relevant outside the immediate Brazilian context. Mabe Bethônico’s artistic practice operates in this fuzzy elusive space, where soft and hard memory meet and converge. Her art successfully turns narratives around, fills voids and uncovers histories that have been silently living among us. The text below is based on an interview she kindly gave us. Nevertheless, for the sake of brevity and to observe the formality of the Portfolio section, we have turned the questions into themes. Therefore, this is the artist’s ‘curated’ testimony that, in a different setting, would most likely have taken a different form.